Celebrate love SG : an initiative to maintain relationship satisfaction in couples in Singapore - Chan, Amy Beth Xin Hui (2015)
Celebrate Love SG is a communications campaign created, organised and executed by four final year undergraduate students at the Wee Kim Wee School of Communication and Information. Targeted at couples in committed relationships, Celebrate Love SG aimed to emphasise the importance of appreciation in romantic relationships. Relationship satisfaction has decreased over the past two decades in Singapore. While there have been past initiatives on relationships, they were aimed at encouraging relationships for singles or at promoting healthy marriages. In view of this, Celebrate Love SG was conceptualised to support relationship satisfaction by promoting the recognition of and appreciation for expressions of love in relationships. A three-phase execution plan was developed to encourage reflection among the target audience of their partners’ acts of appreciation. The campaign employed the use of offline and online outreach to expand its impact. This report explains the research that provided insight for the development of the campaign strategies. Details of the campaign tactics and publicity efforts are outlined. A thorough analysis of the campaign activities was conducted, and it was determined that the campaign was successful in achieving its impact and output objectives. Finally, the campaign’s achievements and limitations were discussed. As maintaining relationship satisfaction requires continuous reinforcement, the team concluded that future initiatives are recommended to continue the campaign’s efforts.